Determinants of anemia among pregnant women: A hospital based cross sectional study - Kalpana, P.; Kavitha, A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The objective was to study the determinants of anemia among pregnant women. There is a negative effect on the health of the mother and as well as that of the child due to anemia in women with pregnancy. Death rate is more in women who are pregnant and having anemia. The objective of this study was to study the determinants of anemia among pregnant women. Methods: A hospital based cross sectional study was carried out among 40 pregnant women over a period of six months. Demographic data like age, residence, occupation etc was recorded. Obstetric data like gravida, parity, previous LSCS was also recorded. The data was presented as means and student’s t test was applied. Results: The mean age was 23.43±3.4 years. Majority were young between the ages of 19-22 years. Majority belonged to urban residents i.e. 57.5%. 20% of the subjects were found to be illiterate. Majority of the mothers were housewives i.e. 82.5%. Majority were multi-gravida i.e. 60%. Majority had no history of abortions in the past i.e. 75%. Out of total 19 repeat pregnancies, majority i.e. 84.2% had lower segment cesarean section. Majority reported that they had normal menstrual history. The mean hemoglobin level was found out to be 7.94 gm/dl. It was found that the mean hemoglobin level did not differ significantly across age, residence, education, occupation, gravidity, history of abortions, type of delivery but differed significantly by abnormal menstrual cycle. Conclusions: Mean hemoglobin level was more in women with normal menstrual history compared to those women with abnormal menstrual history and this difference was found out to be statistically significant. Hence abnormal menses should be promptly treated, hemoglobin assessed.